Correlation of Evaporation Heat Transfer Inside 8.8 mm and 7.14 mm Horizontal Round Micro-Fin Tubes. Issue 3 (25th February 2019) - Chen, Xu; Li, Wei; Sun, Zhijian; Ren, Yong; Liu, Fu; Xu, Jin-liang
ABSTRACT: Experimental investigations of evaporation heat transfer of R22 and R410A inside a horizontal micro-fin copper tube have been conducted and are reported here. Six micro-fin tubes with inner diameter of 7.14 mm and three micro-fin tubes with inner diameter of 8.8 mm but with different geometric parameters, such as the apex angle, the helical angle, fin height, fin pitch, and starts were tested. The evaporation experiments were taken at a constant temperature of 6°C. Moreover, working conditions of the experiments varied with the mass flux ranging from 100 kg/(m 2 .s) to 400 kg/(m 2 .s). For the evaporation experiments of Tube 1 – Tube 6 with R22, the inlet and outlet vapor quality is set as 0.1 and 0.9, respectively. For the evaporation experiments of Tube 7 – Tube 9 with R410A, the inlet and outlet vapor quality is set as 0.2 and 0.9, respectively. The heat transfer coefficients and the changing trend of the heat transfer coefficients vary among these tubes. The influence of each geometric parameter on the heat transfer performance of the micro-fin tube has been analyzed and is reported. Besides, correlations of evaporation heat transfer inside 8.8 mm or less horizontal round micro-fin tubes were developed.